The implementation of green logistics between the logistics service providers in Kuala Lumpur and Kota Bharu : the perception of lecturers in University Malaysia Kelantan - Lee, Wei Jie; Hoo, Bee Hua; Yaakob, Husna; Abd Rashid @ Rashdi, Juhairah (2015)
The aim of this study was to analyze about the perception of lecturers in University Malaysia Kelantan (UMK) for the implementation of green logistics between the logistics service providers in Kuala Lumpur and Kota Bharu. The literature review presents the major theories and concepts included in green logistics. The researchers were conducting a qualitative research which using the snowballing sampling method. In addition, qualitative semi-structured interviews were used in this study. The researchers using common themes method which divided into four themes such as relevant knowledge of respondent, significance of green logistics, benefit of green logistics and challenges of green logistics to discuss and analyze the collected data. The result showed that green logistics is less implemented in Malaysia due to the lack of awareness of the public. The implementation of green logistics can increase the customer satisfaction and retain their customers as well. In other words, these results showed that the objective of this study was achieved. The findings from this study are the implementation of green logistics may provide the positive impact towards the company’s performance. The awareness of public towards going green activities is less and the information regarding to the issues of green logistics is limited in Kota Bharu rather than Kuala Lumpur. Conclusively, further discussions regarding to the importance of green logistics are acknowledged